2018
DOI: 10.1245/s10434-018-6629-9
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Oncologic Outcomes Following Robotic Liver Resections for Primary Hepatobiliary Malignancies: A Multicenter Study

Abstract: RLS can be performed for primary hepatobiliary malignancies with long-term oncologic outcomes comparable to published open and laparoscopic data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 66 publications
(46 citation statements)
references
References 44 publications
3
42
0
1
Order By: Relevance
“…48 Although the use of robotic technology has not been specifically evaluated for iCCA, encouraging results have been reported in a cohort of patients with different types of hepatic tumours treated by hepatectomy. 49 A recent consensus states that robotic LR is safe and has similar effectiveness to open hepatectomy in patients with hepatic malignances, although the level of evidence supporting this assertion is very low. 50…”
Section: Role Of Lymphadenectomymentioning
confidence: 99%
“…48 Although the use of robotic technology has not been specifically evaluated for iCCA, encouraging results have been reported in a cohort of patients with different types of hepatic tumours treated by hepatectomy. 49 A recent consensus states that robotic LR is safe and has similar effectiveness to open hepatectomy in patients with hepatic malignances, although the level of evidence supporting this assertion is very low. 50…”
Section: Role Of Lymphadenectomymentioning
confidence: 99%
“…Several studies using the da Vinci have been published recently that conclude robotic hepatectomy is a safe, feasible and effective alternative to laparoscopic liver resections. 13,[20][21][22] A study comparing robotic liver surgery with open and laparoscopic procedures demonstrated robotic hepatectomy to be non-inferior in their long term oncologic outcomes. 21 Some authors have also demonstrated that lesions in the right posterior liver segments are safe and feasible for robotic resection.…”
Section: Discussionmentioning
confidence: 99%
“…13,[20][21][22] A study comparing robotic liver surgery with open and laparoscopic procedures demonstrated robotic hepatectomy to be non-inferior in their long term oncologic outcomes. 21 Some authors have also demonstrated that lesions in the right posterior liver segments are safe and feasible for robotic resection. 23,24 A recent meta-analysis showed no difference in the transfusion rate, complication rate, conversion rate, the R1 resection rate and hospital stay between robot assisted and laparoscopic liver resection.…”
Section: Discussionmentioning
confidence: 99%
“…Our study combined data from six different institutions across the United States and Europe of patients diagnosed with hepatocellular carcinoma, cholangiocarcinoma, or gallbladder cancer between 2006 and 2016 who then underwent robotic liver resections (5). We showed that overall survival and disease free survival of patients undergoing robotic liver surgery is comparable to the published data on laparoscopic liver surgery.…”
Section: Presentmentioning
confidence: 99%